A Gum‐Like Lithium‐Ion Battery Based on a Novel Arched Structure. (12th January 2015) - Weng, Wei; Sun, Qian; Zhang, Ye; He, Sisi; Wu, Qingqing; Deng, Jue; Fang, Xin; Guan, Guozhen; Ren, Jing; Peng, Huisheng
<x xml:space="preserve">Abstract</x> Stretchable lithium‐ion batteries (LIBs) consisting of an arch structure and a stretchable anode and cathode are developed using a general strategy. The LIB maintains a remarkable and stable electrochemical performance after hundreds of stretching cycles at a strain of 400%. Compared with other stretchable LIBs, which stretch at the device level, but whose components (electrodes) remain rigid, the component‐level stretchability is here the design key to the LIB's highly stable performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>